[Nucleotide sequence of two exons of the human T-lymphocyte CD4 receptor gene] - Zverev, V; Sidorov, A; Nedospasov, SA; Maliushova, V; Udalova, I; Andzhaparizde, O; Blinov, V (1995)
Genome DNA encoding the N-part of human CD4 gene located in the 15 kilobase (kb) Sau3a restriction fragment was cloned and nucleotide sequence of a part (3430 b.p.) of this fragment determined. Exons 2 and 3, intron 2, and partially introns 2 and 3 of this gene were located in the sequenced fragment. Six Alu repeats and open reading frames (ORFs) coding for proteins very close to C5 and C3 components of the complement were detected in this fragment.